Assessing the Perceived Impact of ICT on Children’s Learning Outcomes in Ajeromi Ifelodun Local Government, Lagos State - AFOLABI, Folashade; ADEBANJO, Adetayo Adekunle (Ilorin Journal of Education, 2023)
The covid-19 pandemic has caused a sudden transformation globally. The education system had to adjust to remote teaching making teaching and learning go online. Though, a lot of advantages have been seen compared to the known traditional method. Many adverse effects accompanied the positive ones which should be given serious attention. Introducing ICT to children at an early stage if not properly monitored could lead to adverse effects on their lives and relationships with others. Therefore, this paper focused on the assessment of the perceived impact of ICT on children’s learning outcomes in Ajeromi-Ifelodun local government area in Lagos State. The research posed three research questions using a descriptive research design. The participating pupils are seventy (70) and their parents filled the out questionnaire through a Google form. The instrument was subjected to content and face validity by experts. The content and reliability coefficient values of the instrument were 0.98 and 0.94 respectively indicating the high-reliability index. The findings of the study indicated that ICT though has advantages if not monitored the adverse effects could be devastating to children’s learning outcomes. The study, therefore, recommended that government, parents, teachers, and other stakeholders should monitor the use of ICT in schools for children and provide a limit for its usage.